A Unique Lassoing Scene from the Mastaba of Akhmerutnisut at Giza (G 2184) - Torres, Inês.
This article analyzes a unique scene from the Giza mastaba of Akhmerutnisut (G 2184), which shows a life-size depiction of the tomb owner holding a rope, ready to throw a lasso. The active participation of the tomb owner in a lassoing scene is unique in the iconographic program of Fifth Dynasty elite tombs. The location of this scene within the mastaba is also unparalleled: it is the first scene on the right (west side) encountered by visitors as they enter the mastaba. To understand this innovative decorative choice, this paper starts by discussing the iconography of lassoing in the Old Kingdom and its meaning in the elite tombs of the same period. The second part of this paper analyzes Akhmerutnisut’s lassoing scene with an analytical framework drawn from visual and material culture studies and focusing on the concepts of monumentality, identity and agency. This study provides a number of possible explanations—none of which are mutually exclusive—to understand why Akhmerutnisut had himself depicted as a monumental lassoer by the entrance of his funerary complex, highlighting the importance of visitor experience and participation in the design of the funerary complexes of the Old Kingdom elite.